Pelatihan Pembuatan Abon Cabai Rawit untuk Meningkatkan Pendapatan Keluarga Petani Di Desa Lepak Timur, Kabupaten Lombok Timur : Training on Making Abon Chili Rawit to Increase Farmer Family Income in East Lepak Village, East Lombok Regency - Wuryantoro; Ayu, Candra; Mandalika, Eka Nurminda Dewi; Sari, Ni Made Wirastika; Supartiningsih, Ni Luh Sri; Danasari, Idiatul Fitri; Bardayanti, Deslin Sarmitha; Putri, Sista Eliyani (Universitas Mataram, 2024)
East Lepak Village is one of the large cayenne pepper producing areas in East Lombok Regency. Cayenne pepper is a commodity that is the choice of farmers in East Lepak Village because the demand is quite high, but at harvest time the selling price of cayenne pepper becomes very low and has the potential to harm farmers. In such conditions, one solution that can be offered is to carry out agro-industrial activities (processing) of cayenne pepper into shredded. The purpose of this service activity is to foster farmers to be more skilled in processing cayenne pepper into shredded cayenne pepper, and to increase farmers' insight into entrepreneurship. Shredded cayenne pepper is a processed chili product in the form of dry, ready to serve, has a high shelf life, is practical to carry and store and has a high selling value. The implementation of the activity was carried out in the form of lectures, discussions, and practice of making shredded cayenne pepper. The material for implementing the activity was delivered directly by the implementation team who was also the resource person, so that the activity could run effectively. The results of the service showed that the participants showed a fairly good response, and participated actively in following the entire series of service activities. There was an increase not only in the cognitive and affective aspects but also in the psychomotor aspects, where there was an increase in the knowledge of the participants, where the participants were able to make and package shredded cayenne pepper ready for market. This success is expected to be able to increase the added value of the cayenne pepper commodity and become a source of additional income for family farmers in East Lepak Village.